RATE OF RETURN: SOME COMMENTS IN ITS APPLICABILITY IN CAPITAL BUDGETING. - Brown, Victor H. (The Accounting Review, 1961)
Abstract An essential phase of a rational capital budgeting process concerns appraising the profitability potentials of recognized opportunities for capital investment. Typically, management must decide upon an effective rationing of capital among the numerous capital proposals recommended to it for adoption. Profitability considerations are manifestly important in such decisions. While the notion of rate of return on investment is commonplace, the term is widely employed to describe a variety of historical and projected mathematical relationships between earnings and investment. In this paper, rate of return refers to that rate of interest which equates through time a project's anticipated cash flows with the initial capital outlay required to adopt rate of return determination explicitly considers all three determinants of a proposal's financial worth and ignores external considerations such as the cost of the capital required to adopt the proposal. Via the discounting procedure, the time value of money is taken into account. A proposal's expected profitability is ex- pressed in a single figure representing the average annual rate of compound interest at which the project's initial investment is expected to be recovered through cash flow generation.